Common Genetic Variants Found in HLA and KIR Immune Genes in Autism Spectrum Disorder - Torres, Anthony R.; Sweeten, Thayne L.; Johnson, Randall C.; Odell, Dennis; Westover, Jonna B.; Bray-Ward, Patricia; Ward, David C.; Davies, Christopher J.; Thomas, Aaron J.; Croen, Lisa A.; Benson, Michael (Frontiers in Neuroscience, 2016)
The “common variant - common disease” hypothesis was proposed to explain diseases with strong inheritance. This model suggests that a genetic disease is the result of the combination of several common genetic variants. Common genetic variants are described as a 5% frequency differential between diseased versus matched control populations. This theory was recently supported by an epidemiology paper stating that about 50% of genetic risk for autism resides in common variants. However, rare variants, rather than common variants, have been found in numerous genome wide genetic studies and many have concluded that the “common variant—common disease” hypothesis is incorrect. One interpretation is that rare variants are major contributors to genetic diseases and autism involves the interaction of many rare variants, especially in the brain. It is obvious there is much yet to be learned about autism genetics. Evidence has been mounting over the years indicating immune involvement in autism, particularly the HLA genes on chromosome 6 and KIR genes on chromosome 19. These two large multigene complexes have important immune functions and have been shown to interact to eliminate unwanted virally infected and malignant cells. HLA proteins have important functions in antigen presentation in adaptive immunity and specific epitopes on HLA class I proteins act as cognate ligands for KIR receptors in innate immunity. Data suggests that HLA alleles and KIR activating genes/haplotypes are common variants in different autism populations. For example, class I allele (HLA-A2 and HLA-G 14bp-indel) frequencies are significantly increased by more than 5% over control populations (Table2). The HLA-DR4 Class II and shared epitope frequencies are significantly above the control populations (Table 2). Three activating KIR genes: 3DS1, 2DS1 and 2DS2 have increased frequencies of 15%, 22% and 14% in autism populations, respectively. There is a 6% increase in total activating KIR genes in autism over control subjects. And, more importantly there is a 12% increase in activating KIR genes and their cognate HLA alleles over control populations (Torres, 2012). These data suggest the interaction of HLA ligand/KIR receptor pairs encoded on two different chromosomes is more significant as a ligand/receptor complex than separately in autism.